Mineral Precipitation by Epilithic Biofilms in the Speed River, Ontario, Canada - Konhauser, K. O. (1994)
Epilithic microbial communities, ubiquitously found in biofilms on submerged granite, limestone, and sandstone, as well as on the concrete support pillars of bridges, were examined in the Speed River, Ontario, Canada. Transmission electron microscopy showed that attached bacteria (on all substrata) were highly mineralized, ranging from Fe-rich capsular material to fine-grained (<1 μm) authigenic (primary) mineral precipitates. The authigenic grains exhibited a wide range of morphologies, from amorphous gel-like phases to crystalline structures. Energy-dispersive X-ray spectroscopy indicated that the most abundant mineral associated with epilithic bacteria was a complex (Fe, Al) silicate of variable composition. The gel-like phases were similar in composition to a chamositic clay, whereas the crystalline structures were more siliceous and had compositions between those of glauconite and kaolinite. The consistent formation of (Fe, Al) silicates by all bacterial populations, regardless of substratum lithology, implies that biomineralization was a surface process associated with the anionic nature of the cell wall. The adsorption of dissolved constituents from the aqueous environment contributed significantly to the mineral formation process. In this regard, it appears that epilithic microbial biofilms dominate the reactivity of the rock-water interface and may determine the type of minerals formed, which will ultimately become part of the riverbed sediment. Because rivers typically contain high concentrations of dissolved iron, silicon, and aluminum, these findings provide a unique insight into biogeochemical activities that are potentially widespread in natural waters.